2020
DOI: 10.21273/hortsci14757-19
|View full text |Cite
|
Sign up to set email alerts
|

Foliage Plants Improve Concentration and Emotional Condition of Elementary School Students Performing an Intensive Assignment

Abstract: This study was conducted to compare the concentration and emotional condition of elementary school students performing an intensive assignment in the presence or absence of foliage plants, using electroencephalography (EEG) and a modified semantic differential method (SDM). In a crossover experimental design, 30 elementary students performed a 3-min intensive age-appropriate arithmetic assignment in the presence or absence of foliage plants. Continuous EEG monitoring in the frontal lobe was performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…This is because children focused on harvesting lettuce during harvesting activities by looking at the color and size of lettuce in the garden, selecting lettuce to be harvested, being careful not to injure other lettuces, and grasping the bottom of the leaf stem to harvest lettuce. In a previous study, Kim et al (2020) also reported that children's brain activity and attention skills were significantly increased when performing tasks in spaces with plants than in spaces without plants. Igarashi et al (2015) reported that the prefrontal lobes of participants were activated when observing plants.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…This is because children focused on harvesting lettuce during harvesting activities by looking at the color and size of lettuce in the garden, selecting lettuce to be harvested, being careful not to injure other lettuces, and grasping the bottom of the leaf stem to harvest lettuce. In a previous study, Kim et al (2020) also reported that children's brain activity and attention skills were significantly increased when performing tasks in spaces with plants than in spaces without plants. Igarashi et al (2015) reported that the prefrontal lobes of participants were activated when observing plants.…”
Section: Discussionmentioning
confidence: 81%
“…This study involved 30 elementary school students between 10 and 13 years of age. In previous studies investigating the psycho-physiological effects of exposure to plants on humans, 30 participants were recruited as a single experimental group without a control group and showed significantly different results (Kim et al, 2020;Oh et al, 2019). Research information was posted on the bulletin boards of churches and apartments near Konkuk University to recruit participants.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations